2021
DOI: 10.3390/nitrogen2020018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nitrogen Treatment by Four Onsite Wastewater Systems in Nutrient-Sensitive Watersheds of the North Carolina Coastal Plain

Abstract: Wastewater may be a source of nitrogen (N) to groundwater and surface waters if not effectively treated. In North Carolina, onsite wastewater systems (OWSs) are used by 50% of the population for wastewater treatment, but most OWSs are not routinely monitored. There is a lack of information regarding the N contributions from OWSs to water resources. Four sites with OWSs were instrumented with groundwater wells near their drainfield trenches to compare N concentrations in groundwater to concentrations in wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The Mg-PT and Na-PT bulk liquid equilibrium pH increased to 7.02 and 7.28, respectively, indicating that the extent of pH increase was due to the removal of NH 4 from solution, raising the pH accordingly. The pHs of the effluent were well within the range desired for discharge (6)(7)(8)(9), indicating that in practice no pH adjustments may be needed. Other P sorption materials, such as Polonite, has a high sorption capacity for phosphorus but effluent wastewater can have pHs of near 12 as hydroxides are released.…”
Section: Phosphate Removal By Clinoptilolite Zeolite Is Improved With...mentioning
confidence: 74%
See 1 more Smart Citation
“…The Mg-PT and Na-PT bulk liquid equilibrium pH increased to 7.02 and 7.28, respectively, indicating that the extent of pH increase was due to the removal of NH 4 from solution, raising the pH accordingly. The pHs of the effluent were well within the range desired for discharge (6)(7)(8)(9), indicating that in practice no pH adjustments may be needed. Other P sorption materials, such as Polonite, has a high sorption capacity for phosphorus but effluent wastewater can have pHs of near 12 as hydroxides are released.…”
Section: Phosphate Removal By Clinoptilolite Zeolite Is Improved With...mentioning
confidence: 74%
“…In several New England coastal counties considered critical resource areas, studies have shown than advanced secondary OWTS targeted to meet the local standard of 19 mg N L −1 do so 0-78% of the time, with their treatment effectiveness heavily dependent on the treatment train of the applied commercial technology and the daily nitrogen loading rates. [6][7][8] Meanwhile, achieving phosphorus reductions is left to natural attenuation in drainfields or requires an additional secondary or tertiary treatment step. 9 Drainfields with high clay content soils do well at removing phosphorus due to their high iron and aluminum content while sandy soils with limited metal oxides do poorly.…”
Section: Introductionmentioning
confidence: 99%